PENERAPAN TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN MATERI KONSEP MOL DI SMK PGRI PONTIANAK - Kinanti, Kinanti; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThis study was conducted to determine (1)  the differences in learning outcomes between students who were given learning Teams Games Tournament and student who were  given group discussion lessons on mole concept materials. (2) the effect of teams games tournament towards the learning outcomes. (3) the difference of motivation between students who were given learning Teams Games Tournament and student who were  given group discussion lessons on mole concept materials of class X SMK PGRI Pontianak. This research used Quasy experiment method with ?nonequivalent control group design?. The sample was taken by using saturated sampling technique. The instrument used were essay test and motivation questionnaire. The results showed that : (1) there are differences in learning outcomes between students who were given Teams Games Tournament learning with student who were given group discussion lessons on mole concept material. (2) Teams Games Tournament give effect of 47,4%  to students? learning outcomes. (3)  There is a difference of  motivation between students who were given Teams Games Tournament learning with student who were given group discussion lessons on mole concept material. Keywords : teams games tournament, learning outcomes, motivation, mole concept.